(untitled) (International Journal of Applied Sciences and Biotechnology, 2017)
Cellulose acetate phthalate (CAP)membrane was interacted separately with aqueous HCl solution and aqueous HCl with sodium dodecyl hydrogen sulphate (SDS) as a surfactant and their characteristic properties were determined on the basis of water content, conductance-time and membrane potential data. The possibility of electrochemical modification of cellulose acetate phthalate membrane upon immobilization of the anionic surfactant (SDS) has been also explored. Variable concentration of HCl solutions were used across a cellulose acetate phthalate membrane for membrane potential. The data has been used to interpret the variation of permselectivity ,effective fixed charge density and Donnan distribution ratio of membrane. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 267-272